2021
DOI: 10.3390/educsci11010019
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Emergency eLearning and Beyond: Experiences and Perspectives of University Educators

Abstract: Due to the COVID-19 pandemic, eLearning became the lifeline of higher education. We explored university educators’ eLearning perspectives, practices, and future adoption intentions. In-depth interviews with 14 educators from a large university in Singapore were conducted. Educators had limited eLearning experience prior to COVID-19 emergency eLearning and expressed strong preferences for in-person sessions. The short notice to switch to eLearning and lack of eLearning experiences created stress and anxiety. Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
157
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(206 citation statements)
references
References 27 publications
5
157
0
6
Order By: Relevance
“…After the four phases of selecting the eligible articles for review, 45 were found to be suitable to be used in this systematic review due to the nature of the respective studies. From the articles, four main aspects of teachers' perspectives on the use of Quizizz could be seen, mainly, effectiveness , feasibility [14,15,19,20,22,23,26,27,31,36,38,41,[43][44][45][46][47][48], difficulty [16,17,19,26,28,31,39,41,43,46,[48][49][50][51][52], and motivation [14,17,[24][25][26]31,32,35,38,40,41,44,45,47,49,50,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the four phases of selecting the eligible articles for review, 45 were found to be suitable to be used in this systematic review due to the nature of the respective studies. From the articles, four main aspects of teachers' perspectives on the use of Quizizz could be seen, mainly, effectiveness , feasibility [14,15,19,20,22,23,26,27,31,36,38,41,[43][44][45][46][47][48], difficulty [16,17,19,26,28,31,39,41,43,46,[48][49][50][51][52], and motivation [14,17,[24][25][26]31,32,35,38,40,41,44,45,47,49,50,…”
Section: Resultsmentioning
confidence: 99%
“…This represents a vast majority of the research articles found, and after reading through the 29 articles, it is safe to say that teachers mostly agree that the platform is effective in the classroom. Teachers from various countries agreed that Quizizz is effective in many ways, especially in helping learners to learn in a fun, interactive, and meaningful environment [15,19,20,24,25]. Quizizz has a high potential to be exploited in a myriad of ways, including for assessment and classroom exercises [29,31,32,37,38].…”
Section: Teachers' Perspective On the Effectiveness Of Quizizzmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Developing e-learning contents and providing el-learning opportunities is one of the areas advancing rapidly. [4,8] E-learning, known as electronic learning, unites two areas, learning and technology. [9] According to Aparicio, Bacao, [9] learning "is a cognitive process for achieving knowledge" while "technology is "an enabler of the learning process".…”
Section: Introductionmentioning
confidence: 99%
“…First, changes in the methods of teaching university students based on the widespread use of remote digital technologies [2,3,4]. Secondly, the creation of favorable conditions during the pandemic for the uptake of educational material and the maintenance of a high level of quality of education, despite the remote communication between students and teachers [5,6]. Third, the needs to adapt the existing open-source learning digital platforms like the Moodle (Modular Object-Oriented Dynamic Learning Environment) based on the Internet to the possibility of a rapid shifting from full-time training to training under condition of the full or partial lockdowns [7,8].…”
Section: Introductionmentioning
confidence: 99%